Psychological Well Being dan Motivasi Kerja Pada Pegawai Dinas Pendidikan - Laksmi, Kinanthi Kawuryaning; Budiani, Meita Santi (Jurnal Psikologi Teori dan Terapan, 2015)
The purpose of this research was to examine the relationship between psychological well being and working motivation of employees. The method used in this study was a quantitative correlational design. The subjects of this study were 64 employees of bureau of education level III at â€œXâ€ city, which were selected by using population sampling technique. Data of psychological well-being and working motivation were obtained by using Likert scales. The technique of data analysis in this study was Pearsonâ€™s product moment.Â The result of this study shows that the coefficient correlation is 0.788 in the Significant level of 0.000. The result means that the hypothesis is accepted, that there is positive correlation between psychological well-being and working motivation. The result also indicates that 78.8% of working motivation influenced by psychological well-being and the rest of it 21.2% influenced by other variables that were not measured in this study.Abstrak:Â Penelitian ini bertujuan untuk mengetahui hubunganÂ psychological well- beingÂ dengan motivasi kerja pegawai. Penelitian ini menggunakan metode kuantitatif korelasional. Subjek dalam penelitian ini ialah 64 pegawai golongan III di Dinas Pendidikan Kota X yang dipilih dengan menggunakan teknik sampling populasi. Data dikumpulkan menggunakan skala likert berupa skalaÂ psycgological well-beingÂ dan skala motivasi kerja. Teknik analisis data dalam penelitian ini adalah uji analisis korelasi. Hasil penelitian menunjukan bahwaÂ psychological well-beingÂ memiliki hubungan yang signifikan dengan motivasi kerja dengan arah hubungan yang positif, dapat dilihat dari signifikansi sebesar 0,000 dan yang artinya sebesar 78,8% pada motivasi kerja dipengaruhi olehÂ psychological well-beingÂ dan sisanya sebesar 21,2% dipengaruhi oleh variabel lain yang tidak diukur dalam penelitian ini.